SAT0120 UNITED STATES RHEUMATOLOGY PRACTICE-BASED REAL-WORLD EVIDENCE OF INFUSION REACTIONS IN RHEUMATOID ARTHRITIS PATIENTS TREATED WITH INTRAVENOUS GOLIMUMAB OR INFLIXIMAB: IMPACT OF PRIOR BIOLOGIC EXPOSURE AND METHOTREXATE UTILIZATION. (2nd June 2020) - Schwartzman, S.; Broadwell, A.; Kivitz, A.; Black, S.; Xu, S.; Langholff, W.; Kafka, S.
Abstract : Background: AWARE (Comparative and Pragmatic Study of Golimumab IV Versus Infliximab in Rheumatoid Arthritis) is an ongoing Phase 4 comparator study designed to provide a real-world assessment of intravenous golimumab (GLM) and intravenous infliximab (IFX) in patients (pts) with rheumatoid arthritis (RA). The study recently reached its primary endpoint (comparison of overall incidence of infusion reactions in GLM- vs IFX-treated pts after 52 weeks) with the last patient reaching 52 weeks of treatment or discontinuation from the study. AWARE also records prior use of biologic medications and concomitant use of methotrexate (MTX). Objectives: To assess the incidence of infusion reactions among GLM and IFX pts reported at baseline by examining the influence of prior biologic exposure or concurrent use of MTX. Methods: AWARE is a prospective, noninterventional, observational, multicenter, 3-year study conducted in the US. RA patients (1, 270 adults) were enrolled at the time of initiating treatment with GLM or IFX. All treatment decisions were made at the discretion of the treating rheumatologist. An infusion reaction was any adverse event that occurred during an infusion or within 1 hour after the infusion of either GLM or IFX. Imputations were not performed on these AWARE data. Data shown are mean ± standard deviation. Results: Demographics are shown in Table 1 and the incidence of infusion reactions in different AWARE cohorts is shown in Table 2 . GLM and IFX pts were comparable in sex and utilization of MTX at baseline. Both age and disease duration of GLM pts was greater than IFX pts by ~2 years. There was a higher proportion of bionaïve pts in IFX-treated group compared to GLM-treated group. Overall, infusion reactions occurred more frequently among IFX-treated pts compared to GLM-treated pts. The difference in infusion reaction rates between IFX- and GLM-treated pts was also evident among subgroups of bionaïve vs non-bionaïve pts, and among MTX non-users vs MTX users (characteristics reported at baseline). GLM pts did not report any serious or severe infusion reactions. These were reported rarely (3/585 pts) in IFX-treated pts. Among GLM and IFX pts with an infusion reaction, 55.6% of GLM and 77.1% of IFX pts had at least one medication for infusion reaction. Infusion reactions accounted for 9.7% and 35.1% of discontinuations due to adverse events in GLM and IFX pts, respectively. Conclusion: Whether bionaïve, non-bionaïve, MTX non-user or MTX user at baseline, the incidence of infusion reactions was notably lower among GLM- vs IFX-treated pts. Serious and/or severe infusion reactions did not occur among GLM pts and were rare among IFX pts. IFX was more commonly administered mediation for an infusion reaction compared to GLM. Infusion reactions accounted for almost four times the number of discontinuations related to adverse events in IFX pts compared to GLM pts. Disclosure of Interests: Sergio Schwartzman Grant/research support from: Janssen Research & Development, LLC, Consultant of: AbbVie, Crescendo Bioscience, Dermtech, Eli Lilly and Company, Gilead Sciences, Janssen Pharmaceutica, Myriad Genetics, Novartis, Regeneron, Samsung, Sanofi, UCB, Speakers bureau: AbbVie, Eli Lilly and Company, Genentech, Janssen Pharmaceutica, Novartis, Pfizer, Regeneron, Sanofi, UCB, Aaron Broadwell Grant/research support from: Janssen Research & Development, LLC, Janssen, Eli Lilly, Consultant of: AbbVie, Amgen, AstraZeneca, Celgene, Eli Lilly, Janssen, Novartis, Pfizer, Sandoz, Speakers bureau: AbbVie, Amgen, Celgene, GSK, Horizon, Janssen, Mallinckrodt, Novartis, Pfizer, Radius, Sanofi-Regeneron, UCB, Alan Kivitz Shareholder of: AbbVie, Amgen, Gilead, GSK, Pfizer Inc, Sanofi, Consultant of: AbbVie, Boehringer Ingelheim, , Flexion, Genzyme, Gilead, Janssen, Novartis, Pfizer Inc, Regeneron, Sanofi, SUN Pharma Advanced Research, UCB, Paid instructor for: Celgene, Genzyme, Horizon, Merck, Novartis, Pfizer, Regeneron, Sanofi, Speakers bureau: AbbVie, Celgene, Flexion, Genzyme, Horizon, Merck, Novartis, Pfizer Inc, Regeneron, Sanofi, Shawn Black Employee of: Janssen Research & Development, LLC, Janssen Scientific Affairs, LLC, Stephen Xu Employee of: Janssen Research & Development, LLC, Wayne Langholff Employee of: Janssen Research & Development, LLC, Shelly Kafka Employee of: Janssen Scientific Affairs, LLC